Sociodemographic, economic, and psychological drivers of the demand for life insurance: Evidence from the German Retirement Income Act - Carolin Hecht; Katja Hanewald (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
We exploit the natural experiment of the 2005 income tax reform in Germany to study the effects of tax incentives on consumer behavior in life insurance markets. Our empirical analysis of sociodemographic, economic, and psychological household characteristics elicited in the German SAVE study shows that two very different consumer groups buy (endowment) life insurance before and after the tax reform. We find that education plays a central role in reactions to the modified tax environment. Our stylized characterization of 'arbitrageur' and 'straggler' buyers will assist both life insurance firms and regulatory authorities design effective policies.
Keywords: D12; D14; D91; G22; K34; 330; life insurance demand; tax incentives; financial literacy; Lebensversicherung; Nachfrage; Einkommensteuer; Steuerreform; Steuerwirkung; Finanzwissen; Deutschland